Do you want to increase IT ambidexterity? Pay attention to paradoxes in projects - Kaneko, Rogério (2020)
Paradoxes, persistent contradictions between interdependent elements, are increasingly common and relevant for organizations, as the business environment gets steadily more unpredictable, ambiguous, and fast. At the same time, organizations are also increasingly digital since information technology is more and more pervasive and powerful. In this context, organizations strive for agility through technology to respond to opportunities and threats more effectively. These responses often take place in the form of IT projects that are exposed to paradoxes, such as control and autonomy, stability and change, and short and long term. Previous studies already identified that organizational agility is positively influenced by IT ambidexterity, the ability to simultaneously explore and exploit IT resources and practices. Theory also describes how certain IT components contribute to IT ambidexterity; however, the literature is silent on a key point: how the ability to effectively manage paradoxes in IT projects influence IT ambidexterity. To contribute to the information systems’ field, we propose a new construct, IT project ambidexterity, and evaluate its influence on IT ambidexterity through an on-line survey with 132 Brazilian IT executives. Survey data were analyzed using the partial least square, structural equation modeling (PLS-SEM) statistical approach. We found that IT project ambidexterity positively and significantly influences IT ambidexterity, a source of organizational agility in a digital and dynamic world.